Growth Response of Local Cassava to Cutting Models and the Number of Buds - Tri Mulya Hartati; Chumidach Roini; Indah Rodianawati (Universitas Sebelas Maret, 2021)
Cassava is one of the local food sources that are widely available in almost every region. Cuttings are used to plant cassava, and these cuttings will produce a number of roots and buds. The main purpose of this study was to evaluate the effect of cuttings slices model and the number of buds on the growth of Tobelo local varieties of cassava. This study employed a factorial Randomized Block Design (RBD), with the cuttings slices model as the first factor, consisting of three levels, namely: flat slice, one-sided slice and two-sided slice. The second factor is the number of buds, which is divided into three levels, 1 bud, 2 buds and 3 buds. The observation parameters in this study include plant height, number of leaves, stem diameter and leaf area. The results have revealed that the model of two-sided sliced cuttings combined with the number of one bud is the most effective treatment in improving the growth of cassava plants of Tobelo local varieties. The models of one-sided and two-sided oblique cuttings slices yield the highest average value for the parameters of plant height, stem diameter and leaf area, while the treatment with one bud tends to give the best results for the growth parameters.